30 anos de dinâmica espaço-temporal (1984-2015) da região de influência do Parque Nacional da Chapada dos Veadeiros – Goiás - Mariana Santos da Silva; Helen Gurgel; Anne-Elisabeth Laques; Bruna Drumond Silveira; Rogério Vidal de Siqueira (Confins)
In the last decades, the Cerrado, considered a hotspot of biodiversity, has faced hard anthropic transformations. An example of this dynamism is the region of Chapada dos Veadeiros, located in the north of the state of Goiás. Located in Central Brazil has an active landscape with several areas used for sustainability and with important socioeconomic transformations linked to modern agriculture. In this context, the main objective of this paper is to develop an integrated analysis of the space-time dynamic toward a better characterization of the regional scenario. We used the land cover data for a period of 30 years (1984-2015), as well as socioeconomic indicators, local physical characterization and the integration of the road network, using geotechnologies for their analysis. The results show strong relationships between land-use changes, the density of road infrastructure and the declivity of landforms in the region. When these information were integrated with socioeconomic indicators, it was highlighted that the region is unequal and with specific dynamics, and can be divided into three distinct regions: Cavalcante and Teresina de Goiás: a stigmatized north; Alto Paraíso de Goiás and Colinas do Sul: a diversified center; and São João d'Aliança: an explored south. The agricultural border in the southern part, now reaches this iconic region. Considering this kind of use affects environment negatively with loss of natural cover, generating direct impacts to soil and water quality, and fauna and flora dynamism, it creates negative effects to the quality of life of the local population. Beyond that, it affects the natural scenic beauty, which is strongly related to tourism, locally adopted as an alternative to the current economic development model. The findings of this article reinforce the idea that a more sustainable relationship between agriculture and conservation of the natural environment needs to be achieved in the region.